The Relationship between Feeding Practices and Personal Hygiene Practices with Stunting Incidents in the Coastal Area of Muna Regency - Kadir Bahar, Abdul; Tasnim, Tasnim; Amraeni, Yunita (Waluya The International Science of Health Journal, 2024)
Introduction: Stunting is a condition of failure to thrive in babies (0-11 months) and toddlers (12-59 months) resulting from chronic malnutrition, especially in the first 1,000 days of life so that the child is too short for his age. Malnutrition occurs when the baby is in the womb and in the early days after the baby is born, but stunting only appears after the child is two years old. This research aims to find out about the Stunting Incident Prediction Model in the Coastal Area of ​​Muna Regency. Method: This type of research is quantitative using a cross-sectional design (Cross Sectional Study). The sample in this study was 322 mothers who had toddlers aged 12-59 months in the coastal area of ​​Muna Regency. Result: Results: Of the 322 normal toddlers, there were 258 toddlers or (80.1%) and 64 stunted toddlers or (19.9%). Of the 322 respondents who had good feeding practices, there were 283 respondents or (87.9%) and those who had poor feeding practices were 39 respondents or (12.1%). Of the 322 respondents whose hygiene practices were good, there were 186 respondents or (57.8%) and those with poor hygiene practices were 136 respondents or (42.2%). Conclusion: The nutritional status of children under five is very important to pay attention to because it has a large and long-lasting impact on the child's health status, physical and mental development as well as the child's productivity as an adult.